EFFECT OF RURAL DEVELOPMENT POLICY AND EMPOWERMENT OF ENHANCING FOOD SECURITY IN SAROLANGUN REGENCY, JAMBI PROVINCE - Feri Wijaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Food Security is one of the economies of local communities in Indonesia, rehabilitated and reconstructed by the efforts of adequate food availability for households. However, not all areas to manage the existing resources well be the center of attention, carrying out development evenly. Therefore the role of government and the community is very important in improving food security. This study aimed to analyze the influence of Rural Development Policy and Community Empowerment against Improved Food Security in Sarolangun, either partially or collectively sama.Metode research is quantitative, and Mechanical Sampling and descriptive qualitative data analysis techniques. The results showed that there are significant rural development policy, the low influence of community empowerment and rural development policy and community empowerment together affect the improvement of food security. Indicators of the availability of clean food staples and the percentage of areas close to 5km from a health facility is to support and be an attraction in this study. Recommendations of the study: (1) The collection and compilation of data and documents on local food security, (2) Strategic Plan pangandaerah resistance and (3) food security program is short, medium and long term. KEYWORDS : Policies, Empowerment and Food Security